(untitled) (Phoenix: International Multidisciplinary Research Journal ( Peer reviewed High Impact Journal ), 2025)
The study critically examines the role of management lessons derived from the Bhagavad Gita and the leadership strategies of Chhatrapati Shivaji Maharaj, emphasizing their relevance in modern management education. Rooted in the Indian Knowledge System (IKS), these teachings offer valuable insights into leadership, strategic decision-making, ethics, and resilience. The Bhagavad Gita provides profound philosophical and managerial wisdom, focusing on duty, self-discipline, and crisis management. Similarly, Shivaji Maharaj’s governance model highlights visionary leadership, people-centric administration, and tactical excellence. This review explores their integration into management curricula, fostering ethical leadership and strategic acumen among future managers. The study aims to bridge traditional wisdom with contemporary management practices, making a case for an inclusive and value-driven approach in business education.